Microwave-based gluconic acid-catalyzed extraction of chitin-glucan extract from industrial Aspergillus niger biomass with functional activities (Kuwait Journal of Science)
Industrial Aspergillus niger biomass can be a valuable source of biopolymers with antioxidative and prebiotic properties. To achieve this proposal, ethanol extraction of soluble free compounds with antioxidant activity was separated from native biomass, and high-performance liquid chromatography/mass spectrometer (HPLC-MS) was further performed. Then, the pretreated biomass was submitted to microwave (MW) pressurized heating with a gluconic acid-catalyzed process. The yield of ethanol-isolated chitin-glucan extract was 4.09 ± 0.26 % (dry basis). The chitin-glucan chemical composition consisted of glucose (86.61 ± 0.69 % w/w) and amino-sugar (0.76 ± 0.03 % w/w). Spectroscopic and chromatographic methods confirmed the characterization of the chitin-glucan extract. The radical scavenging activity of the native, pretreated biomasses, chitin-glucan, and ethanol-soluble compounds by DPPH assay were 81, 20, 69, and 51%, respectively. The determination of the prebiotic activity by substrate-induced respiration (SIR) indicated production of 0.54 ± 0.02 and 0.44 ± 0.04 μg CO2–C/g/h for Lactobacillus plantarum and Bifidobacterium lactis, respectively. The proposed extractive method using MW, an emerging technology and gluconic acid, is an eco-friendly process for obtaining chitin-glucan. This method does not generate chain deacetylation linear chitin. Chitin-glucan presents prebiotic and antioxidant activities, generating added value as a functional additive. © 2024